Differential diagnostics of bullous dermatoses - A. A. Kubanov; L. F. Znamenskaya; T. V. Abramova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Bullous dermatoses are the diseases characterized by vesication and erosion of skin and/or mucos coats, production of autoantibodies against the structural components of epidermis and/or derma. The most frequent diseases of these disorders are pemphigus, bullous pemphigoid, dermatitis herpetiformis, beningn familial chronic pemphigus (Gougerot Hailey-Hailey disease).Diagnostics of bullous dermatoses is based on assessement of clinical signs, results of cytological and histological studies and immunological tests. However none of the current diagnostic methods allows to reveal bullous dermatosis severally and with absolute certainty. Consequently it is necessary to perform wide range of clinical and laboratory tests for early diagnosis and treatment order.